하동군 녹차산업 혁신클러스터 육성방안 - 박문호 (한국농촌경제연구원, 2005)
The objective of this study is to proactively deal with government- driven "Regional Agriculture Cluster Policy" and the changing environment surrounding the green tea industry, which the specialized industry of Hadong- gun, and to develop strategies and action plans for an innovative green tea industrial cluster to strengthen the industry's competitiveness. The findings of the study indicate that Hadong-gun is best suited for creating the innovative green tea industry cluster in terms of the natural environment, the historical and cultural surroundings, and the industrial and economic environment. However, the survey results of local experts on the regional capability of innovation show that the region lags behind in several areas, such as supporting industries by sector and the innovative capability of the "development council" and farmers. Meanwhile, in order to accelerate innovation of other industries, development projects linked to eco-friendly tea cultivation, the modernization of processing facilities, and green tourism should be given top priorities. The development strategies for the Hadong Green Tea Industrial Cluster to enhance its competitiveness are as follows: First, it is important to produce top quality tea products. To this end, it is essential to develop unique Hadong green tea products with top quality, establish a distinguished tea brand, set up a quality control system covering the entire processes from production to distribution, and put the brand promotion system in place. Second, the industrialization strategy to turn Hadong into a hub of green tea-related technology should be initiated. For example, Hadong Green Tea Research Center should be established. Third, the strategy to build the green tea industry complex should be able to vitalize green tourism as well based on the local tourism and cultural resources. Fourth, the above-mentioned strategies can be implemented in three stages, such as laying groundwork, specialization, and maturing. In the stage of laying groundwork, offering intensive education, establishing pertinent network, setting a stage for production, technology development, processing, distribution, public relations and green tourism, and developing a premium Hadong green tea with its brand can be pursued. In the stage of specialization, it is necessary to form a Green Tea Bio-Tech Industrial Cluster in order to facilitate the industrialization of Hadong green tea and to push ahead with various programs which will strengthen the industrial foundation. In the last maturing stage, the globalization of the Hadong tea industry should be pursued by creating a Green Tea Well-being Valley in main cultivation areas, such as Hwagae and Akyang.